Let sinx = s, cosx = c
I_n = I s^n dx
= I s^(n-2)*s^2 dx
= I s^(n-2)(1 - c^2) dx
= I s^(n-2) - s^(n-2)c^2 dx
= I_(n-2) - s^(n-2)c^2 dx
So u = c
du = - s
v = 1/n-1*s^(n-1)
dv = s^(n-2)*c
so I_n = I_(n-2) - [1/(n-1)*s^(n-1)*c + I 1/(n-1)*s^n]
I_n*(n - 1) = I_(n - 2)*(n - 1) - [s^(n-1)*c] - I_n
n*I_n = I_(n - 2)*(n - 1) - (s^(n-1)*c)
I_n = (n - 1)/n*I_(n - 2) - 1/n[s^(n - 1)*c] (n != 0)
sub in the 0 and pi/2 (should have done it earlier, but it dosn't matter)
I_n = (n - 1)/n*I_(n - 2) - 1/n[0 - 0]
I_n = (n - 1)/n*I_(n - 2)
EDIT: Note, the same trick can be used for (cosx)^n